Augmented Reality 3D Heart as Learning Media at Midwifery Lab University of 'Aisyiyah Surakarta - Rahmad Ardhani; Sigit Setiyanto; Ita Permatahati (International Journal of Computer and Information System (IJCIS), 2022)
Abstract— Utilization of Information Technology (IT) in the process of delivering information has been developed rapidly. Currently, the latest technology used in the delivery of information is Augmented Reality (AR) technology.. Pada teknologi Augmented Reality (AR), pengguna dapat menvisualisasikan objek atau benda bersejarah dalam bentuk 3 dimensi. Augmented Reality (AR) has the advantage of being interactive and real time so Augmented Reality (AR) is widely implemented in the field of education as a medium to introduce historical objects which are cultural heritage or objects related to a science. Augmented Reality (AR) has the advantage of being interactive and real time, so Augmented Reality (AR) is widely implemented in various fields. Based on the explanation of the study, researchers are interested in conducting research using information technology in the health sector, by making Augmented Reality (AR) modeling to facilitate the community and midwifery students in providing learning about human organs, especially the heart which can be used digitally without having to dissect human organs and bringing him a modeling of the heart with the presence of a 3D heart organ provides convenience in learning to the public about the function and structure of the heart digitally.Keywords :3D, Augmented Reality, Heart 3D Design.